The 'true' genus Alona Baird, 1843 (Crustacea: Cladocera: Anomopoda): position of the A. quadrangularis-group and description of a new species from the Democratic Republic of Congo - van Damme, Kay; Dumont, Henri J. (Zootaxa, 2008)
We describe Alona kolwezii n. sp. from the Afrotropics and provide a morphological comparison with the type species of the genus A. quadrangularis. Past classification problems of Alona indicate a potential complexity of evolution and radiation in these smaller Aloninae. We present a historical overview of systematic approaches to the genus Alona aiming towards an increased understanding of Aloninae phylogeny. A proposed delineation of “true” Alona Baird, 1843 is presented as the quadrangularis-group, comprising A. quadrangularis, A. kolwezii and A. boliviana. We discuss the phylogenetic position of the quadrangularis-group with a redescription of its limbs, interspecific variability and morphological adaptations to an epi-benthic mode of life.